SERS microsensors for pH measurements in the lumen and ECM of stem cell derived human airway organoids. Issue 22 (23rd February 2023) - Skinner, William H.; Robinson, Nicola; Hardisty, Gareth R.; Fleming, Holly; Geddis, Ailsa; Bradley, Mark; Gray, Robert D.; Campbell, Colin J.
Abstract : SERS microsensors (SERS-MS) are polymer microparticles coated in gold nanoparticles and functionalised with mercaptobenzoic acid. SERS-MS were incorporated into human airway organoids to measured pH optically. Abstract : Patient derived organoids have the potential to improve the physiological relevance of in vitro disease models. However, the 3D architecture of these self-assembled cellular structures makes probing their biochemistry more complex than in traditional 2D culture. We explore the application of surface enhanced Raman scattering microsensors (SERS-MS) to probe local pH gradients within patient derived airway organoid cultures. SERS-MS consist of solid polymer cores decorated with surface immobilised gold nanoparticles which are functionalised with pH sensitive reporter molecule 4-mercaptobenzoic acid (MBA). We demonstrate that by mixing SERS-MS into the extracellular matrix (ECM) of airway organoid cultures the probes can be engulfed by expanding organoids and report on local pH in the organoid lumen and ECM.